2021
DOI: 10.18632/oncotarget.27954
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses of urine RNA reveal tumor markers for human bladder cancer: validated amplicons for RT-qPCR-based detection

Abstract: Non-invasive clinical diagnostics of bladder cancer is feasible via a set of chemically distinct molecules including macromolecular tumor markers such as polypeptides and nucleic acids. In terms of tumor-related aberrant gene expression, RNA transcripts are the primary indicator of tumor-specific gene expression as for polypeptides and their metabolic products occur subsequently. Thus, in case of bladder cancer, urine RNA represents an early potentially useful diagnostic marker.Here we describe a systematic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…It rather describes the feasibility of this approach. This methodology has been applied in many studies describing RNA-based tumor makers, including microRNA and RNA polymerase II transcripts in human cells [21][22][23][24][25]. In the light of these successful applications of the protocol, this work describes a robust and quantitative technology for RNA-based marker detection in urine samples for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It rather describes the feasibility of this approach. This methodology has been applied in many studies describing RNA-based tumor makers, including microRNA and RNA polymerase II transcripts in human cells [21][22][23][24][25]. In the light of these successful applications of the protocol, this work describes a robust and quantitative technology for RNA-based marker detection in urine samples for diagnostic purposes.…”
Section: Discussionmentioning
confidence: 99%
“…The examples of marker detection shown in Figure 6, in particular KRT20, seem to reach the gold standard level of the diagnosis of BC. This has warranted a transcriptome analysis of urine RNA obtained from BCa patients and healthy donors [25] from which we currently derive new markers for BCa with increased sensitivity and specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of S100A6 has been reported for example in the culture medium of decidual cells [ 142 ] or cerebellar granule neurons treated with myelin-associated glycoprotein [ 143 ]. It has been also detected in extracellular matrix of Wharton’s jelly [ 144 ], amnion fluid [ 145 ], pancreatic juice [ 107 , 146 ], urine [ 147 , 148 ] and tears [ 149 ]. Recent results have shown that S100A6 is present in nasal lavage fluid [ 150 ], and its level is elevated in the nasal swabs of COVID-19 patients [ 151 ].…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%
“…There are numerous reports linking changes in S100A6 level in body fluids with various diseases. For example, serum levels of S100A6 are positively correlated with the progress of four different types of cancer: gastric cancer, non-small cell lung cancer, ovarian cancer and urinary bladder cancer [ 42 , 148 , 154 , 155 , 156 , 157 , 158 , 159 ]. Based on these data, it has been proposed that the serum level of S100A6 can be used as a biomarker in detecting these types of cancer and serve as an indicator of their progress.…”
Section: Extracellular S100a6—a Marker Of Pathological Statesmentioning
confidence: 99%
“…Analysis of BCa cell lines [ 40 ] of the RNA transcriptome revealed linear and circular transcripts of calcium-binding protein S100 6 (S100A6) and translocation-related membrane protein 1 (TRAM1) as highly promising potential markers for this disease. This study showed that the S100A6/TRAM1 ratio has a high ability to diagnose BCa based on urinary RNA.…”
Section: What Is New In the Last Two Years?mentioning
confidence: 99%